The Teacher Preparation in Integrating ICT Into Innovative English Classroom at Junior High School 2 Rambah Samo - Mahlia, Rika; Siswandi, Siswandi (Journal of English and Arabic Language Teaching, 2023)
The study was aimed to examined how the process of the teacher preparation in integrating ICT. The effectiveness of the integrating of information and communication technologies (ICT) in teaching and learning is to the recent educational innovations. Based on the researchers’ initial research, the researcher found the teacher preparation in integrating ICT at junior high school 2 Rambah Samo. Researcher use qualitative research that helps researcher to find out the teacher preparation in integrating ICT. The participants in this study were English teachers at junior high school 2 Rambah Samo. For this study researcher gave questions in the interview transcribed. Finally, the results of the analysis show that the process of the teacher preparation in integrating ICT into innovative English classroom.